Educational Leadership Integration In Interdisciplinary Learning And Institutional Innovation For Sustainable Social Development - Nur Efendi (Journal of Studies in Academic, Humanities, Research, and Innovation, 2024)
This study investigates the integration of educational leadership in interdisciplinary learning and its contribution to institutional innovation and sustainable social development at MAN 2 Trenggalek. The research aims to examine how leadership practices shape interdisciplinary learning, how these practices support institutional innovation, and how the interaction among these elements contributes to broader social outcomes. A qualitative case study design was employed to capture in-depth insights within a natural educational setting. Data were collected through semi-structured interviews, observations, and document analysis involving the principal, teachers, and administrative staff. The findings reveal that educational leadership integrates vision, collaboration, and value orientation in facilitating interdisciplinary learning practices. Teachers engage in cross-disciplinary planning, reflective dialogue, and contextual teaching strategies that enhance student engagement and learning relevance. Institutional innovation is reflected in adaptive instructional programs, collaborative evaluation processes, and continuous refinement of teaching practices. The study also identifies a dynamic relationship in which leadership supports learning, learning drives innovation, and innovation contributes to sustainable social development. These findings demonstrate that leadership integration is essential in developing responsive and socially relevant educational environments.